Implementing priority setting frameworks: Insights from leading researchers. Issue 12 (December 2016) - Angell, Blake; Pares, Jennie; Mooney, Gavin
Highlights: This paper provides insights from leading researchers for health-systems implementing priority-setting frameworks. Leadership and a health economist to guide implementation were vital to success. Limited evidence exists linking priority-setting frameworks to efficiency or equity outcomes. Abstract: In spite of a substantial literature developing frameworks for policymakers to use in resource allocation decisions in healthcare, there remains limited published work reporting on the implementation or evaluation of such frameworks in practice. This paper presents findings of a targeted survey of 18 leading researchers around the implementation and evaluation of priority-setting exercises. Approximately one third of respondents knew of situations where recommendations of priority-setting exercises had been implemented, one third knew that recommendations had not been implemented and the final third responded that they did not know whether recommendations had been adopted. The lack of evidence linking the implementation of priority-setting recommendations to equity and efficiency outcomes was highlighted by all respondents. Features identified as facilitating successful implementation of priority-setting recommendations included having a climate ready to accept priority-setting, good leadership or a 'champion' for the priority-setting process and having a health economist to guide the process. Successful disinvestment was very uncommon in the experience of the researchers surveyed. Recommendations emerging from Program Budgeting and Marginal Analysis exercises appeared to be more widely implemented than those coming from alternative processes. Identifying if the process was repeated following the initial process was suggested as a means to measure success.